IKLIM KOMUNIKASI ORGANISASI - Mizal Septiawan; Mohamad Muspawi; Fiona Eliffa Zahri; Azzahra Nuraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research examines the climate of organizational communication along with the elements that shape it. The study is grounded in the idea that effective communication is essential for improving organizational performance. A qualitative method with a literature review approach was employed, using academic references and digital sources as the primary data. The findings reveal that a constructive communication climate significantly contributes to organizational achievement by supporting coordination, increasing employee motivation, and enhancing work efficiency. Furthermore, the study identifies several strategies for strengthening communication climate and presents examples of their application within organizations. In conclusion, the research underlines that a well-managed organizational communication climate can positively influence productivity and overall organizational performance